(untitled) (The Science Post, 2026)
Digital eye strain and dry eye symptoms are increasingly prevalent among university students due to prolonged screen exposure and extended hours spent in indoor study environments. University libraries, classrooms, and computer laboratories may also contain volatile organic compounds (VOCs) released from paints, furniture, carpets, cleaning products, printers, and other indoor materials, which may negatively affect ocular health. While previous studies have separately examined indoor air pollution and digital eye strain, limited research has investigated their combined effect on tear film stability among students. This study aims to examine the relationship between VOC exposure in university study environments, tear film stability, and digital eye strain. A cross-sectional observational study will be conducted among university students aged 18–30 years who regularly use digital devices for academic purposes. Indoor environmental parameters, including VOC concentration, carbon dioxide levels, temperature, and relative humidity, will be measured in selected university study spaces such as libraries, classrooms, and computer labs. Participants will complete standardized questionnaires, including the Ocular Surface Disease Index (OSDI) and Computer Vision Syndrome Questionnaire (CVS-Q), to assess dry eye and digital eye strain symptoms. Tear film stability will be evaluated using Tear Break-Up Time (TBUT). Statistical analyses will determine associations between environmental exposure and ocular outcomes.